Women Farmers as Entrepreneur in the Sebatik-Nunukan Border, North Kalimantan Province - Rudiatin, Endang; Rahman, Abdul; Equatora, Muhammad Ali; Sulhan, Sulhan (Jurnal Ilmiah Peuradeun, 2021)
Policies in the economic and development sector still place men as the main actors, women only as “task assistants” in economic activities. The women of Liang Bunyu village in West Sebatik District make Seaweed farming a source of household income and become a leading commodity in village economic development. The women in the village bind seaweed farming for the nursery. A job that men are reluctant to do, but the most important part of the production process. This paper discussed how Sebatik women play a crucial role in making seaweed cultivation a household business. It will be an essential input for the local government policy of developing a household business driven by housewives. The research method used was a qualitative description with an ethnographic approach to make participant observations and in-depth interviews are accurate in collecting data and field findings. The research found that Sebatik women had the prospect to be an entrepreneur. It's just that Sebatik's economic development does not necessarily increase women's empowerment. Not many Sebatik women farmers think about selling seaweed as a processed product, which is more economically valuable and profitable. Education and community culture were the main causes, even though kinship and ethnic networks could function as economic capital. Sebatik woman farmers need government support in both policy regulation and practical assistance, especially in entrepreneurial training.